2016
DOI: 10.1371/journal.pone.0147488
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Copper and Zinc on the Single Molecule Self-Affinity of Alzheimer’s Amyloid-β Peptides

Abstract: The presence of trace concentrations of metallic ions, such as copper and zinc, has previously been shown to drastically increase the aggregation rate and neurotoxicity of amyloid-β (Aβ), the peptide implicated in Alzheimer’s disease (AD). The mechanism of why copper and zinc accelerate Aβ aggregation is poorly understood. In this work, we use single molecule force spectroscopy (SMFS) to probe the kinetic and thermodynamic parameters (dissociation constant, Kd, kinetic dissociation rate, koff, and free energy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…This dimer structure switches from parallel to anti-parallel in the presence of Cu 2+ and this process is regulated with the occupied binding sites of Cu [ 140 ]. Moreover, the same scholars later demonstrated that the nanomolar content of Cu 2+ has no impact on peptide–peptide bonds of dityrosine-linked β-amyloid dimers [ 141 ]. Another study has shown that Cu 2+ ions binding results in structural variations in the β-amyloid dimers, causing oligomer-defining interactions, including N-terminal interaction in them [ 142 ].…”
Section: Copper Ion Implication In Admentioning
confidence: 99%
“…This dimer structure switches from parallel to anti-parallel in the presence of Cu 2+ and this process is regulated with the occupied binding sites of Cu [ 140 ]. Moreover, the same scholars later demonstrated that the nanomolar content of Cu 2+ has no impact on peptide–peptide bonds of dityrosine-linked β-amyloid dimers [ 141 ]. Another study has shown that Cu 2+ ions binding results in structural variations in the β-amyloid dimers, causing oligomer-defining interactions, including N-terminal interaction in them [ 142 ].…”
Section: Copper Ion Implication In Admentioning
confidence: 99%
“…However, literature reports on the properties of these variants differ to some extent, a heterogeneity that is explained from the differences in protocols applied, in particular regarding the preparation of monomer Aβ, but also in terms of analytical methods applied [61]. [436]. Wild-type murine Aβ contains three different amino acids within the metal binding N-terminal:…”
Section: The Fibrillated Peptidesmentioning
confidence: 99%
“…In fact, many studies indicated that zinc homeostasis is an important factor for the prevention and treatment of AD. However, others indicated that zinc may stimulate Aβ aggregation causing more harmful in AD [70], [71]. These conflicting reports were explained by the fact that 1 mM dose of zinc may be harmful for AD patients as zinc may reinforce Aβ aggregation and result in an increase in the number or size of neuronal Aβ plaques while low zinc (50 μM) exerts protective effects against Aβ-40 induced toxicity [72].…”
Section: Clinical Impact Of Insulin Degrading Enzyme (Ide) On Alzheimmentioning
confidence: 99%